Contribuições psicanalíticas de Erich Fromm para a compreensão do nazismo - Marques, Oswaldo Henrique Duek (2015)
This work analyses Erich Fromm s psychoanalytical contributions to the understanding of Nazism and its intrinsic anti-Semitism by conducting a theoretical research in Psychoanalysis, while taking into account the historical and philosophical basis. In the first chapter we focus on the historical aspects of Nazism and anti-Semitism. In the second chapter, we discuss psychoanalytical contributions from de the Freudian field in order to reflect on the question of Nazism from a psychoanalytical point of view, as an introduction to Fromm s ideas on this topic. In the third and final chapter, we study aspects of Nazism and anti-Semitism in Fromm s works. In the conclusion, we present Fromm s main psychoanalytical contributions to these themes. Through a critical and reflexive analysis this work attempts to demonstrate this author s crucial contribution to the psychoanalytic understanding of Nazism and Anti-Semitism. The value of this research resides in the fact that no deep and specific study on Fromm s psychoanalytic contributions to the understanding of these topics has been found. The referred issues are still current in today s world, as they reveal, from a psychoanalytical standpoint, the mechanisms that unleash the discrimination and intolerance in totalitarian regimes